2017
DOI: 10.1177/2167696817722470
|View full text |Cite
|
Sign up to set email alerts
|

Social Role Transitions and Perceived Adulthood Status

Abstract: The purpose of this study was to investigate which social role transitions typically related to the advent of adulthood are associated with the perceived adulthood status of Greek men and women aged 25-29 and 30-35. Participants were 313 (27.8% male, overall average age 29.9 years) Greeks who answered questions concerning the achievement of adult role transitions (getting married, bearing children, moving away from parental home, becoming financially independent, and employed) and their perceived adulthood sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This explanation is further supported by the recent finding that young Greek men express more hopelessness than women, and although they exhibit increased intention for alternative small-scale political action, they experience decreased political efficacy and a distrust or mistrust in traditional politics (Davou, 2017). In addition, in another recent Greek study, there were indications that emerging adulthood may last beyond age 30 for men (Vleioras & Mantziou, 2017). If we take all these data into account, we can conclude that, in our sample of unmarried studying youth, females seem to have made more steps toward adulthood and present a more mature and/or resilient profile compared to males.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This explanation is further supported by the recent finding that young Greek men express more hopelessness than women, and although they exhibit increased intention for alternative small-scale political action, they experience decreased political efficacy and a distrust or mistrust in traditional politics (Davou, 2017). In addition, in another recent Greek study, there were indications that emerging adulthood may last beyond age 30 for men (Vleioras & Mantziou, 2017). If we take all these data into account, we can conclude that, in our sample of unmarried studying youth, females seem to have made more steps toward adulthood and present a more mature and/or resilient profile compared to males.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, factors representing a mixture of individualistic and collectivistic criteria emerged as the predominant conception of adulthood in another study (Galanaki & Leontopoulou, 2017). In addition, another recent Greek study (Vleioras & Mantziou, 2017) showed that the achievement of two role transitions, that is, marriage and semiautonomous and independent living, decreased the feeling of being an emerging adult only after the age of 30 and only for women, whereas it had no effect on people aged 25–29.…”
Section: Emerging Adulthood and Transition To Adulthood In Greecementioning
confidence: 99%
“…Extensive evidence from the sociological and developmental psychology literature shows that in several countries the attainment of traditional role markers (the "Big Five" markers), that is, finishing education, starting a career, leaving the parental home, marriage, and parenthood, plays a significant role in the experience of the emerging adulthood features and the pathways to adulthood (Vosylis, 2021). It has also been found in many studies that the attainment of some or all of these markers increases the subjective sense of adulthood (Arnett, 2003;Barry et al, 2009;Benson & Furstenberg, 2006;Eliason et al, 2015;Kins & Beyers, 2010;Kuang et al, 2024;Luyckx et al, 2008;Shanahan et al, 2005;Vleioras & Mantziou, 2018, for Greek adults older than 25; Zupančič et al, 2014). There is limited research on which specific achieved markers, that is, traditional markers such as role transitions and/or psychological qualities such as independence, are typical of the young people who perceive themselves as adults.…”
Section: Personal and Contextual Factors Accounting For The Subjectiv...mentioning
confidence: 99%
“…Another found that after the Great Recession, young women (and first-generation college students) had the most difficult transition to employment, which is likely to affect later work opportunities as well as family formation (Aronson 2007). Outside of the United Studies, some studies have begun to explore gender differences, which seem to vary by country, suggesting that they are bound up with cultural context (Crocetti et al 2015;Negru 2012;Sirsch et al 2009;Vleioras and Mantziou 2017). Crocetti and her colleagues (2015) argue that findings from this research suggest that women may have a more difficult transition to adulthood than do men.…”
Section: A Universal Transition To Adulthood?mentioning
confidence: 99%